Histopathological Evaluation of Gastric Biopsies and its Association with Endoscopic Findings - Khadka, Pooja; Thapa, Rojin; Shrestha, Manisha; KC, Shiva Raj (Nepalese Medical Journal, 2025)
Introduction: Gastrointestinal disorders include a range of conditions, both non-neoplastic and neoplastic, contributing to significant global morbidity and mortality. The prevalence of these gastric diseases exhibits geographical variability. Endoscopy has been proven to be a breakthrough in the diagnosis of gastric lesions, but histopathology is considered the gold standard. This study aims to shed light on the occurrence of diverse patterns of non-neoplastic and neoplastic gastric diseases in patients undergoing endoscopic biopsies at Patan Hospital. Materials and methods: This cross-sectional study, conducted over 1 year in the Department of Pathology, Patan Academy of Health Sciences, included 117 patients undergoing endoscopic gastric biopsies. Results: A diverse range of gastric diseases was observed across a broad age spectrum, spanning from 18 to 85 years, with a mean age of 57.2 years and a female preponderance of 0.7:1. Biopsy samples from the antrum constituted the majority at 55.6%. The prevalence of H. pylori was 20.5%. There was a statistically significant association between endoscopic findings and histopathological diagnosis (p-value <0.05) despite some discrepancies. Conclusions: The association between endoscopic findings and histopathological diagnoses is robust, demonstrating high sensitivity and specificity. Based on the outcomes of this study, it can be inferred that the rationale behind targeted endoscopic biopsies is well-founded. Nevertheless, it is crucial to emphasize that endoscopy alone is insufficient, and the inclusion of biopsy and histopathology is imperative.